Development of Problem-Based Learning History Learning Module to Improve Critical Thinking Ability and Learning Achievement - Masfiyah, Masfiyah; Nasuha, Munthoha; Kusrina, Tity (Journal of English Language and Education, 2025)
History learning tells the events that occurred in the past, present and future. In its delivery, the teacher uses lecture or conventional methods and the reference book used is less interesting. Researchers tried to develop a feasible problem-based learning-based history module, analyzing the critical thinking skills and learning achievement of students after using this learning module. The development of this learning module uses Research and Development (R D) with the ADD method (Analysis, Design and Development). Data collection techniques in this study used interviews, observations, questionnaires and tests. The population in this study were students of class X State High School in Brebes totaling 72 people with a sample of 36 students in the experimental class and 36 students in the control class. The research results of the problem-based learning module can improve students' critical thinking skills and learning achievement. The results of media expert validation showed 89.7% with very valid/acceptable criteria and material experts showed 93% with very valid/acceptable criteria. Teacher response to the history learning module was 93% with a very positive category and student response to the learning module was 81% with a very positive category. The test results of critical thinking skills and learning achievement of students have increased the use of problem-based learning modules in the history learning process themed development of Hindu Buddhist kingdoms in the archipelago is more effective than using the lecture model.